Immunogenicity and safety of an intradermal ChAdOx1 nCoV-19 boost in a healthy population - Nawamin Pinpathomrat; Porntip Intapiboon; Purilap Seepathomnarong; Jomkwan Ongarj; Ratchanon Sophonmanee; Jariya Hengprakop; Smonrapat Surasombatpattana; Supattra Uppanisakorn; Surakameth Mahasirimongkol; Waritta Sawaengdee; Supaporn Phumiamorn; Sompong Sapsutthipas; et al. (npj Vaccines, 2022)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic. Two doses of an inactivated SARS-CoV-2 vaccine (CoronaVac) have been shown to be insufficient to protect against variants of concern (VOCs), while viral vector vaccines remain protective against the infection. Herein, we conducted a preliminary study to evaluate the safety and immunity in an adult population who received the conventional 2 dosage-regimen of inactivated SARS-CoV-2 vaccine; with an additional intradermal ChAdOx1 nCoV-19 reciprocal dosage (1:5). An Intramuscular ChAdOx1 nCoV-19 booster was also included as a control. Immediate and delayed local reactions were frequently observed in the fractional intradermal boost, but systemic side effects were significantly decreased compared to the conventional intramuscular boost. The anti-RBD-IgG levels, the neutralising function against delta variants, and T cell responses were significantly increased after boosting via both routes. Interestingly, the shorter interval elicited higher immunogenicity compared to the extended interval. Taken together, a reciprocal dosage of intradermal ChAdOx1 nCoV-19 booster reduces systemic adverse reactions and enhances non inferiority humoral and cellular immune responses compared to a full dose of intramuscular boosting. These findings provide for an effective vaccine management during the shortages of vaccine supply.